PERBEDAAN PENGETAHUAN SEBELUM DAN SESUDAH PENYULUHAN PENGELOLAAN SAMPAH PADA MASYARAKAT (Health Publica, 2023)
The waste problem is a social phenomenon that needs attention from all parties because every human being must produce waste, on the other hand, people do not want to be close to garbage.Handling of waste is still a challenge because there is still waste generation. The effectiveness and efficiency of waste handling. Therefore, it is necessary to have a waste handler at the district/city level. This study aims to analyze differences in knowledge of waste management in Jalan Letjend Sarbini Margajaya, South Bekasi in 2022. This study uses a cross-sectional quantitative research type, namely data related to the independent variable and the dependent variable, collected at the same time. Primary data collection was obtained from questionnaires and secondary data collection was the name of the residents from the head of RT 002. Respondents in this study were 30 people. Data analysis was carried out univariate and bivariate using the normality test and then continued with the Wilcoxon test because there was an abnormal data distribution. The results of this study indicate that there is a difference in knowledge before and after counseling about waste management. With a p-value in the normality test of 0.01/data not normally distributed, it was continued with the Wilcoxon test and obtained a p-value of 0.00 <0.05 then it was stated that there was a difference in knowledge before and after the waste management counseling in RT002 RW 001 Margajaya, South Bekasi.